The Effect of Alternative E-mail Contact Timing Strategies on Response Rates in a Self-administered Web Survey. Issue 4 (November 2017) - Lewis, Taylor; Hess, Karl
The Federal Employee Viewpoint Survey is an annual survey of over 800, 000 permanently employed civilian personnel from 87 agencies. First administered in 2002, the web-based survey measures a broad range of employee perceptions, attitudes, and behaviors, serving as a valuable tool for human resources managers to determine which aspects of an organization are working well and which may require intervention. The data collection protocol begins by sending all sampled individuals an initial invitation to participate. Thereafter, nonrespondents are sent weekly reminder e-mails. These notifications are typically sent on Tuesday mornings. In this article, we present results from an experiment investigating two alternative protocols varying when survey notification and reminder e-mails are sent. Interestingly, the stable Tuesday morning strategy produced a significantly higher response rate than the two alternatives, and we analyze timestamp information from one of the alternatives to help provide insight as to why.